Effect of Products Diversification on Performance of Transport Companies in Rwanda: A Case of Translift Limited - Bosco, Ndungutse; Njenga, Samson (International Journal of Strategic Management, 2024)
Purpose: The study's general objective was to assess the impact of product diversification on the performance of transport companies in Rwanda. Examining the impact of strategic positioning on firm performance, mainly through the lens of Translift Limited, offers valuable insight into the effectiveness of strategic management practices within the Rwandan context, aiding in the development of tailored strategies for sustainable business growth and economic development in the region. The research was grounded on Resource-Based View Theory. Methodology: The study adopted a descriptive survey involving both qualitative and quantitative approaches. Qualitative analysis included a review of existing literature on strategic positioning, while quantitative analysis involved collecting and analyzing data from Translift Limited. The target population comprised 150 managers of Translift Limited. The sample size of 115 was determined using Slovin's formula. A combination of purposive and random sampling techniques was adopted. The study used both primary and secondary data. Primary data was collected through a questionnaire, while secondary data included peer-reviewed published journal articles. Qualitative data from interviews and open-ended survey responses were analyzed thematically. Data was coded to categorize responses and identify key concepts or ideas. This process helps organize the qualitative data for further analysis. Quantitative data from closed-ended survey questions was analyzed using descriptive statistics such as frequencies, percentages, means, and standard deviations. Qualitative and quantitative data were triangulated to corroborate findings and enhance the validity of the results. The data was presented in tables and figures where frequency, percentage, mean and standard deviation was used. The study interprets the analyzed data in light of the research objectives and theoretical framework. Findings: The results from the regression analysis demonstrate that several predictor variables significantly influence firms' performance in Rwanda. Specifically, products diversification (β = 0.214, p = 0.020), exhibit positive standardized coefficients, indicating a positive relationship with firm performance. These findings suggest that firms in Rwanda can enhance their performance by diversifying their product offerings, investing in marketing activities, maintaining high-quality service standards, and building substantial trademark equity. However, it's worth noting that the perceived quality of service did not reach statistical significance at the conventional alpha level of 0.05. Overall, the model explains a significant portion of the variance in firms' performance, indicating the importance of these factors in driving business outcomes in Rwanda. In conclusion, the study underscores the importance of strategic factors such as product diversification, marketing efforts, perceived quality of service, and trademark equity in driving firm performance in Rwanda. Unique Contribution to Theory, Practice and Policy: These findings provide valuable insights for businesses operating in the Rwandan market, highlighting the significance of adopting comprehensive strategies prioritizing customer satisfaction, brand development, and market differentiation to achieve sustained success. Based on the study's findings, it is recommended that firms in Rwanda focus on diversifying their product offerings, investing in marketing efforts, maintaining high-quality service standards, and building substantial trademark equity to enhance their performance in the market.